(untitled) (Journal of Economic Research & Business Administration, 2016)
In this article, relevance of reasonable management of borrowed funds of enterprises is considered. It shows the importance of sustainable funding through borrowed funds for enterprises, given the positive aspects of the use of borrowed capital. Solved the problem by attracting (disabilities of borrowed resources, the need of collateral, limited domestic investment; difficulties in the use of foreign investment, an increase in interest rates), and by the use of borrowed resources companies in Kazakhstan (the generation of financial risk, lower rate of return; dependence on market fluctuations financial markets, the ability of creditors to monitor individual decisions; project mismatch). Produced concrete analysis of every problem by combining Kazakh practical situation. We consider their reasons and consequences. Based on these issues, given some actual proposals from the three sides of the enterprises, banks and the state, based on the real situation in Kazakhstan.